Molecular Characterization of Some Virulence Genes and Antibiotic Susceptibility Pattern among Uropathogenic Escherichia coli Isolated from Patient in Zakho City/Iraq - Marwa S. Ibrahim; Haval M. Khalid; Wijdan M. S. Mero (Zanco Journal of Pure and Applied Sciences, 2020)
Uropathogenic Escherichia coli (UPEC) is one of the most causative agents which causing urinary tract infections (UTIs) in humans. This study involved the prevalence of the virulence genes among UPEC isolated from patients in various hospitals in Zakho city from July 2018 until January 2019 and their susceptibility to different commonly used antimicrobial agent against UPEC. The different culture media were used for the identification of Escherichia coli (E. coli). Out of 400 samples, 141 (35.25%) strains of UPEC were isolated from enrolled patients. The antibiotic susceptibility toward different antibiotics was varied among the isolates. Imipenem was the most potent antibiotic with a resistant rate of only 2.84%. While the isolates were resistant to most screened antibiotics, with the highest rate 96.45% to Amoxicillin/ clavulanic. The resistant rates decreased toward other antibiotics at rates varied from 93.62% for Amoxicillin to 43.97% for Norfloxacin. Fifty-seven isolates were selected for PCR analysis, according to the resistance of E.coli to various antibiotics. The selected samples were successfully amplified for E. coli identification by producing a single band of a target uidA gene. In this study, the virulence related genes were detected in only 35 (61.40%) isolates out of 57 isolates. The distribution of the virulence related genes that included; afa, sfa, hly, cnf and pai were 28.07%, 17.54%, 26.32%, 22.81% and 22.81%, respectively. The study highlight that multidrug resistance UPEC harbors multiple virulence genes circulating in this setting.